Klotho, vitamin D and homocysteine levels during acute episode and remission periods in schizophrenia patients. (3rd April 2019) - Yazici, Esra; Mutu Pek, Tugba; Guzel, Derya; Yazici, Ahmet Bulent; Akcay Ciner, Ozlem; Erol, Atila
Abstract: Aim: Neurodegenerative processes are effective in schizophrenia. However, the underlying causes of the symptoms and associated factors have not yet been fully elucidated. Recent research has focused on the relationship between neurodegeneration and vitamin D, Klotho and homocysteine levels. In this study, we aimed to investigate this relationship in schizophrenia. Method: This study included 30 schizophrenic inpatients, 30 schizophrenic outpatients in remission and 28 healthy volunteers as the control group. The psychiatric diagnoses of our patients were evaluated according to DSM-IV criteria. The Positive and Negative Syndrome Scale (PANSS), the Global Assessment of Functioning (GAF) scale and the Clinical Global Impression (CGI) scale were used for clinical measurements. Serum Klotho, homocysteine, vitamin D, vitamin B12 and folic acid levels were analyzed using ELISA and compared with clinical properties. Results: The PANSS scores and CGI scores were higher in schizophrenic inpatients than outpatients, and the GAF scores were lower ( p   < 0.05). Three groups were compared for Klotho, homocysteine and vitamin D serum levels; Klotho levels were elevated but the difference was not statistically significant ( p  > 0.05). However, vitamin B12, folic acid and homocysteine levels were higher in schizophrenic patients than the control group ( p  < 0.05). Conclusions: Higher levels of homocysteine with concomitant higher levels of vitamin B12 and folic acid suggest a relationship of this pathway with schizophrenia. Differences in Klotho levels were elevated but it was not significant. Replication studies to investigate probable associations with larger samples are needed.